Blueberries effects in experimental diet-induced prediabetes: a focus on renal impairment. (24th June 2020) - Alves, A; Preguiça, I; Barbosa, A; Vieira, P; Martins, D; Nunes, S; Viana, S; Reis, F
Abstract: Introduction Benefits arising from blueberry (BB) consumption are well-described in type 2 diabetes evolution and inherent complications. Lending further support to this thesis, previous work from our group unequivocally demonstrates BB supplementation efficacy to manage prediabetic hepatic liver steatosis. Whether a similar effect also holds truth in early renal impairment is an unsolved issue. Objectives To address blueberry juice (BJ) ability to exert renoprotective effects in experimental prediabetes. Methodology Diet-induced prediabetes [high-sucrose (35% Hsu) and high-fat (60% HF)] was developed in adult male Wistar rats through the ingestion of HSu for 9 weeks supplemented by HF for another 14 weeks (HSuHF, n = 16). On W9, half of the former animals orally received BJ (25g/kg BW, HSuHF+BJ). Control animals (n = 8) received standard diet during the entire protocol. Functional [serum and urinary creatinine, uric acid, glucose; glomerular filtration rate (GFR)], structural [H&E and Oil Red O staining] and molecular [triglycerides content and inflammation (RT-qPCR, WB)] markers of renal injury were assessed along with metabolic profile. Results Even though diet-induced glucose intolerance, insulin insensitivity and plasmatic hypertriglyceridemia were significantly ameliorated upon BJ treatment, this nutraceutical intervention was unable to halt or slow down renal lipidosis and glomerular crescent-like lesions apart from a slight amelioration of both GFR and IL-6 levels in HSuHF-treated rats. Conclusion Unlike previous results clearly demonstrating the ability of BJ nutraceutical intervention to afford protection against metabolic impairment and hepatic steatosis evolution in experimentally diet-induced prediabetes, only a modest renoprotective effect was observed in functional and morphological renal endpoints. Future studies are warranted to dissect the divergent effects of BJ on early liver and kidney impairment.